DRESS syndrome potentially induced by allopurinol and triggered by influenza vaccine - Solak, Berna (BMJ Case Rep, 2016)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome, also known as drug-induced hypersensitivity syndrome (DHIS), is an acute, potentially life-threatening disease that includes skin rash, fever, haematological abnormalities and multiorgan involvement. Although its aetiopathogenesis is not exactly known, it is thought that inefficient drug detoxification leading to the accumulation of drug reactive metabolites causes autoimmune responses in skin and some internal organs, alters immune responses and induces reactivation of viral infections in people who have genetic predisposition. To the best of our knowledge, only one case of DRESS syndrome has been reported after delivery of the influenza vaccine, but the drug that induced the reaction in that case was sulfasalazine. We report a case of a 64-year-old woman, receiving allopurinol, who developed DRESS syndrome after taking the influenza vaccine.